CULTURAL AND CONTEXTUAL VARIATION OF ANTHROPOMORPHIC METAPHORS IN THE ENGLISH AND UZBEK LANGUAGES (American Journal of Interdisciplinary Research and Development, 2026)
Cultural and contextual variations in anthropomorphic metaphors, focusing on how different languages and societies attribute human characteristics to non-human entities. It examines the role of culture, environment, history, and social context in shaping metaphorical expressions, drawing on comparative studies and cognitive linguistic theories. Anthropomorphic metaphors, which imbue non-human entities such as animals, objects, or natural phenomena with human traits, emotions, or intentions, are a universal feature of language and thought. However, their expression and interpretation vary significantly across cultures and contexts due to differences in worldview, environment, and social practices. This article examines how cultural beliefs, historical contexts, and situational factors influence the use and perception of anthropomorphic metaphors. By analyzing examples from English and Uzbek linguistic traditions and social settings, it highlights the interplay between universal cognitive tendencies and localized cultural frameworks. The introduction provides a foundation by defining anthropomorphism and its metaphorical applications, followed by the main text, which explores variations in religious, literary, and everyday contexts. The conclusion synthesizes findings and suggests implications for cross-cultural communication.